A Class of Solutions for the Hybrid Kinetic Model in the Tumor-Immune System Competition. (8th May 2013) - Cattani, Carlo; Ciancio, Armando
Abstract : In this paper, the hybrid kinetic models of tumor-immune system competition are studied under the assumption of pure competition. The solution of the coupled hybrid system depends on the symmetry of the state transition density which characterizes the probability of successful occurrences. Thus by defining a proper transition density function, the solutions of the hybrid system are explicitly computed and applied to a classical (realistic) model of competing populations.